Clinical utility of beta-hydroxybutyrate measurement in the management of physiological ketosis at home in children under 5 - Vanelli, Maurizio; Mastrorilli, Carla; Fainardi, Valentina; Iovane, Brunella; Scarabello, Chiara; Veronese, Piero; Fanelli, Umberto; Incerti, Tiziana; Tchana, Bertrand; Dodi, Icilio; Di Mauro, Dora (Acta Biomedica Atenei Parmensis, 2019)
Aim: To verify the possible advantages of 3- β-hydroxybutyrate (3HB) measurement compared to urinary assay of ketones during an intercurrent disease managed at home. Methods: Twelve Pediatricians were asked to enroll at least 4 patients aged 3 to 5 years, affected by an intercurrent illness and showing at least one of symptoms reliable to ketosis. Recruited patients were submitted to the simultaneous assay of 3HB in capillary blood and ketones in urine at 3 (T3) and 6 hours (T6) from the first measurement (T0). For urinary and blood ketone detection commercial tests were used. Results: Thirty-eight children (4.36±2.60 years old; 25 boys) were enrolled into the study. At T0 all children showed 3HB levels (1.2-3.2 mmol/L), but only 10 of them (26.3%) associated also urinary ketone bodies (2 to 4+). In response to 3 hour treatment (T3) with a glucose solution, 3HB values decreased in 19 (0,8-1,8 mmol/L) and normalized in 13 children (